Qualidade dos periódicos científicos: um modelo-síntese para avaliação com foco nos aspectos extrínsecos e intrínsecos indiretos da publicação - Carla Cristina Vieira de Oliveira (2017)
The scientific journals enable the dissemination of new research results, legitimize new disciplines and disseminate knowledge among many other functions. The exponential growth of journals in universities which was facilitated by the recent technological transformations that enabled journals in electronic format, motivated this research on the quality of scientific journals. The literature on the quality of scientific journals can be organized into two sets of studies: the first examines the editorial process (considering aspects related to management itself, such as editorial staff, submission rules, evaluation deadlines, etc.) and the second focuses on the outcome of scientific communication (assessing the level of impact of an article in a specific scientific community). In this context, this research focuses on the first aspect, related to the editorial process, addressing both extrinsic criteria and indicators (data that present the formal aspect of the publication) and intrinsic ones (data that make it possible to evaluate the periodical considering its content or indirect aspects that verified this quality). The research problem involved the synthesis of the diversity of criteria and indicators. The general objective was to develop a broad model that would bring together in a single instrument the quality aspects of the journals presented in the literature, the entry and stay requirements of the main multidisciplinary indexers and the general parameters of the CAPES Qualis 2016 considerations for scientific journals. This is a descriptive research which used bibliographical and documentary research to collect data. In the first phase of the research the criteria and indicators, which were presented in 23 studies, were compiled from the requirements of four indexes: Web of Science, Scopus, SciELO and Latindex, and the meeting of Qualis 2016 considerations from the 49 knowledge areas. From these, a synthesis model was developed to evaluate the quality of electronic journals. In the second phase, this model was tested through a case study in periodicals with Qualis A1 to B1 belonging to the Web Portal of Journals of UFMG (Portal de Periódicos UFMG). It was observed with the case study that the analyzed scientific journals are very timid in marketing actions and visibility of their publications. Among the most recurrent indirect intrinsic aspects in the qualitative and well-valued studies currently in Qualis, the item "indexer" was reported in only 16 of the 23 periodicals evaluated. It is noteworthy that although 17 participate in some social network, only 7 disclose it on their homepage. In the aspects that make possible an analysis of the internationalization of these publications, there was a movement in the translation of the periodicals, the summaries, the availability of the home page in English and the tendency to make abstract and keywords available in more than two languages. It is hoped that the model, product of this study, can be used by editorial teams as a road map for the improvement of their publications. As a perspective of future studies we suggest refinement of the model for specific areas of knowledge and the inclusion of merit evaluation of publications through content analysis with expert support